Oil and Protein Stability in Some Camelina (Camelina sativa L. Crantz) Genotypes - İlhan Subaşı; Yusuf Arslan; Safure Güler; Halil Hatipoğlu; Servet Abrak; Arzu Köse (Turkish Journal of Agriculture: Food Science and Technology)
Camelina sativa L. Crantz., which draws attention with its non-food use (biodiesel, animal feed etc.) against the increasing demand for oilseeds worldwide, is a good alternative plant. It is important to identify suitable and stable genotypes for regions along with high protein and oil content. The purpose of this study, camelina genotypes of Turkey in 3 different locations (Ankara, Ankara, Eskisehir) to investigate the quality characteristics in terms of genotype environment interactions in unirrigated and unfertilized conditions. 36 different genotypes, purified lines by negative selection, were analysed with 3 standard genotypes with augmented trial design. Environmental (E), genotype (G) and G × E interactions, which are sources of variation for protein and oil content, have been shown to be important. Oil and protein content were found ranged from 34.35%-37.88% and 25.76%-27.64% respectively. We have obtained important findings in our study to see the performance of Camelina sativa, and the possibility of alternative oil plants for these regions. İn terms of correlation of protein ratio and oil ratio, genotypes with high value that were least affected by each other were determined. The results showed that genotype selection by regions is important in terms of protein and oil ratio.